ILLUMINATING THE FUTURE: ADVANCES IN TARGETED GENE THERAPY AND OPTOGENETICS IN THE TREATMENT OF INHERITED RETINAL DISEASES - Dominika Nowak; Adam Zarzycki; Patrycja Długosz; Magdalena Próchnicka; Aleksandra Gradek; Marcin Sawczuk; Julia Tarnowska; Filip Szydzik; Bartosz Żegleń; Jan Noskowicz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Inherited retinal diseases (IRDs) are a group of disorders that lead to progressive vision loss, for which no effective treatments have previously been available. Advances in molecular biology have enabled the development of gene therapies and innovative strategies such as optogenetics, offering hope for improvement or restoration of visual function. Aim: The aim of this work is to present the current state of knowledge regarding gene therapies used in IRDs, with particular emphasis on their mechanisms of action, possibilities for personalization, integration with other methods, and the potential of optogenetics as an alternative in advanced stages of the disease. Methods: A literature review was performed using PubMed, Google Scholar, Scopus, and Web of Science. Thirty-nine English publications relevant to inherited retinal diseases and gene therapies were selected. Studies covered mechanisms, efficacy, safety, and diagnostic advances. Irrelevant or methodologically weak papers were excluded. Results: Therapies based on AAV vectors, CRISPR/Cas9 techniques, prime editing, and antisense oligonucleotides demonstrate effectiveness depending on the type of mutation and disease stage. Optogenetics enables the restoration of light sensitivity regardless of the mutation, even in the absence of photoreceptors. Combining gene therapy with other methods, such as stem cells or neuroprotection, enhances therapeutic potential. Conclusions: Gene and optogenetic therapies are transforming the treatment approach for IRDs. Selecting strategies based on the molecular background and disease stage enables a personalized approach. Technical and regulatory challenges remain, but development trends indicate a real possibility of effective treatment for many forms of IRDs.